The effect of Wheatley's strategy on learning the skills of handling and rolling with a soccer ball for second-year middle school students. (Damu Journal of Sport Sciences, 2024)
The developments witnessed by the world and the vast scientific progress in all areas of life, including the educational field, require those in charge of the educational process to pay attention to all its aspects by bringing students to a state of skillful and technical performance and applying any skill and mastering it correctly. This depends on a special strategy that is compatible with those skills and mastering them to achieve educational goals. From this, the research aims to identify the effect of the Whitley strategy in learning to perform the skills of handling and rolling with a football for second-year middle school students, and to identify the differences in learning to perform the skills of handling and rolling with a football for second-year middle school students between the experimental and control groups. The experimental method was used in the style of two equivalent groups (experimental, control) with a pre- and post-test. The research community was determined by second-year middle school students in Al-Madhatiya Intermediate School for Boys affiliated with the Directorate of Education of Babylon Governorate for the academic year (2023-2024) and their number is (192) students, and the research sample was selected with (32) students divided equally into two experimental and control groups, where educational units were applied according to the Whitley strategy to learn to perform the skills of handling and rolling with a football for students, amounting to (8) units, for a period of (4) weeks and at a rate of two educational units per week, with a time of (45) minutes, and the steps of the Whitley strategy were applied (educational tasks, cooperative groups, participation), and the research came out with a set of conclusions, including: The Whitley strategy has a positive effect on learning to perform the skills of handling and rolling with a football for students, and that applying the three stages of the Whitley strategy (educational tasks, cooperative groups, participation) gave a broader understanding of the two skills, and among the recommendations recommended by the researcher: Using the Whitley strategy in learning the technical performance of football skills because it is one of the modern interactive strategies, and emphasizing the use of modern strategies in physical education lessons and staying away from traditional methods and methods.